Lussazioni del carpo - Rampoldi, M.; Antonietti, G.; piccioli, A. (Lo Scalpello - Journal, 2018)
CARPAL INSTABILITIESCarpal instabilities are uncommon and challenging lesions resulting from high energy traumas, often affecting youngpatients. They can result in significant morbidity and disability if inadequately treated. Their anatomy is complexand some aspects of their pathomechanisms still need to be clarified. The diagnosis is often difficult and can be missedin up to 25% of cases, especially in pure ligamentous lesions. Treatment must be prompt, and open anatomicreduction of any carpal malalignment is essential for a successful outcome.